Response of Sorghum bicolor L. to Residual Phosphate on Two Contrasting Soils Previously Planted to Cowpea or Maize - Tola Omolayo Olasunkanmi; Ezekiel Akinkunmi Akinrinde (International Journal of Agronomy)
Proper fertilizer nutrient management through adequate utilization of the residual value coupled with healthy crop rotation contributes significantly to sustainable crop production. This study was conducted to evaluate the direct and residual effects of two rock phosphate (RP) materials on two contrasting soils previously planted with either the cereal crop or the leguminous crop. The effectiveness of the RP materials as substitute for the conventional P fertilizers was evaluated using single superphosphate as reference at the Department of Agronomy, University of Ibadan, Ibadan, Nigeria. The experiments were 2 × 2 × 4 factorial in completely randomized design. The test crops in the first cropping performed better on the slightly acidic loamy sand than on the strongly acidic sandy clay loam. Performance of each crop was improved by P supply in the first and second cropping. Single superphosphate proved to be more efficient than the RPs in the first cropping but not as effective as MRP in the second cropping. In the second cropping, sorghum performed better on the soil previously cropped to cowpea while Morocco RP had the highest residual effect among the P-fertilizer sources. It is evident that rock phosphates are better substitutes to the conventional phosphorus fertilizers due to their long term residual effect in soils. The positive effects of healthy rotation of crops as well as the negative effects of low soil pH are also quite obvious.